DEVELOPMENT OF SAMBAS SONGKET WEAVING MSMEs FROM THE PERSPECTIVE OF SHARIA ENTREPRENEURSHIP - Muhammad Rio (Adisam Publisher, 2025)
MSMEs play a vital role in the national economy and in preserving local culture. In Sambas Regency, West Kalimantan, the songket weaving industry is not only a source of livelihood but also a symbol of the cultural identity of the Malay community. However, weaving MSMEs still face challenges such as limited capital, market access, and business governance. Sharia entrepreneurship offers an alternative approach that emphasizes blessings, justice, and spiritual values in running a business. This study aims to analyze how the development of Sambas weaving MSMEs can be directed in accordance with the principles of sharia entrepreneurship. The method used is a descriptive qualitative study using a literature approach and field observations. The results indicate that the integration of sharia principles can encourage more sustainable and ethical MSME development.